Examining Balloon Expulsion Testing as an Office-Based, Screening Test for Dyssynergic Defecation: A Systematic Review and Meta-Analysis. (November 2018) - Shah, Eric; Farida, Jeremy; Menees, Stacy; Baker, Jason; Chey, William
Abstract Objectives Balloon expulsion testing (BET) is recommended to evaluate for dyssynergic defecation in patients with chronic constipation (CC). However, it remains poorly standardized and is limited to specialized centers. Our goal was to assess the clinical utility of balloon expulsion as an initial test for dyssynergic defecation and to determine appropriate testing parameters. Methods We performed a literature search to identify cohort studies of unselected subjects with CC and case-control studies of subjects with/without dyssynergic defecation. We defined dyssynergic defecation by constipation symptoms and a positive reference test (anorectal manometry [ARM], defecography, or electromyography [EMG]). We performed a meta-analysis using a bivariate mixed-effects regression model to assess summary sensitivity, specificity, and area under the curve (AUC) with 95% confidence intervals (CI). We conducted a meta-regression to investigate individual test parameters and demographic variables. Results We identified 15 eligible studies comprising 2090 individual assessments of BET. Among cohort studies, the AUC was 0.80 (95% CI: 0.61–0.91) with 70% sensitivity (95% CI: 52–83%) and 77% specificity (95% CI: 70–82%). In pooling cohort and case-control studies, the AUC was 0.84 (95% CI: 0.68–0.93) with 70% sensitivity (95% CI: 53–82%) and 81% specificity (95% CI: 75–86%). Subject positioning (seated vs. left lateral decubitus) did not significantly affect test performance in cohort (p  = 0.82) or case-control (p  = 0.43) analysis. Most studies evaluated 50–60 mL water insufflation. Test performance was not significantly affected by varying the maximum allowed expulsion time between 1 to 5 min. Age and gender likely accounted for significant study heterogeneity between studies. Choice of reference test, continent of study, and year of study did not significantly affect test performance. Discussion We report an optimized BET protocol. The performance characteristics of BET could support its use as a point of service test to screen for dyssynergic defecation in chronically constipated subjects.